Planning Development of Sustainability Tourism of Jikomalamo Beach in Ternate City, North Maluku Province - Habib, Supriadi M. Hi; Wahjoedi, Wahjoedi; Haryono, Agung (PT. EQUATOR SINAR AKADEMIA, 2024)
The tourism sector is a mainstay of Indonesia to increase revenue, both from the national level to the regional level. the level of development and optimal management of tourism has significant potential to increase the economic growth of a region, therefore, it needs proper planning, especially in the context of decision-making and policy. One of the areas that are developing this tourism area is the city of Ternate, north Maluku province, which is developing jikomalamo beach tourism using the guidelines of the regional long-term development plan and the vision and mission of Ternate city. This research uses a quantitative approach that is analyzed using SWOT, intending to determine the order of priority for planning the development of the jikomalamo beach tourism area based on the Tourism Development Master Plan document. The results of this study indicate that all the strengths, weaknesses, opportunities, and threats that have been owned by the tourist destination are quite good if analyzed comprehensively. This can be seen from the results of the analysis which reveals that the strengths and opportunities possessed by Jikomalamo beach tourism have a higher average value than the weaknesses and threats. However, in the development of the beach tourism area, there is no cooperation between the government and the local community so the development process does not guarantee sustainability in the development of these tourist destinations